PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PERTAMBANGAN PERIODE 2018-2021 - Widodo, Andre Setya; Annisa, Annisa (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of firm size leverage variable on audit delay. Leverage in this study is proxied by DER (debt to equity ratio) and the size of the company's natural asset logarithm, and audit delay is calculated from the audit report date minus the financial statement book closing date. The population in this study were mining companies for the 2018-2021 period, then 14 companies were selected as a sample. The analytical method used in this study is the panel data regression method using EVIews 9. The results of this study prove that the debt to equity ratio has a positive effect on audit delay and firm size has a positive effect on audit delay.